2018
DOI: 10.1097/hp.0000000000000862
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Population Monitoring Using Whole-Body Counters in Response to the Fukushima Nuclear Accident

Abstract: Whole-body counter measurements of residents of Fukushima Prefecture have been extensively performed after the Fukushima Dai-ichi Nuclear Power Plant accident in March 2011. These measurements have demonstrated that the levels of internal contamination with radioactive cesium (Cs and Cs) in the residents are very low. This article provides an overview of and lessons learned from these whole-body counter measurements with emphasis on the technical problems encountered, and it discusses the effective use of whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…In WBC measurements over the period between June 27 and July 28, 2011, the ratios of subjects with the presence of both 134 Cs and 137 Cs in adults and children were 28.8% and 4.1%, respectively [21]. An overestimation of the cesium intake is also likely to occur in children based on an acute intake scenario on potentially the earliest day [17]. On the other hand, it has been found that the cesium detection rate tends to be higher in late evacuees from areas near the FDNPP in the case of adult subjects, suggesting that a trace of the early intake would appear in the WBC measurements until about half a year after the accident [22,23].…”
Section: Estimation From Direct Measurements For Cesiummentioning
confidence: 98%
See 2 more Smart Citations
“…In WBC measurements over the period between June 27 and July 28, 2011, the ratios of subjects with the presence of both 134 Cs and 137 Cs in adults and children were 28.8% and 4.1%, respectively [21]. An overestimation of the cesium intake is also likely to occur in children based on an acute intake scenario on potentially the earliest day [17]. On the other hand, it has been found that the cesium detection rate tends to be higher in late evacuees from areas near the FDNPP in the case of adult subjects, suggesting that a trace of the early intake would appear in the WBC measurements until about half a year after the accident [22,23].…”
Section: Estimation From Direct Measurements For Cesiummentioning
confidence: 98%
“…These measurements have been continued to the present; the number of measurements has reached 341,430 as of September 2019 (http://www.pref.fukushima.lg.jp/site/portal/ps-wbc-kensa-kekka.html). Details on the WBC measurements conducted in the prefecture have been described elsewhere [17].…”
Section: Estimation From Direct Measurements For Cesiummentioning
confidence: 99%
See 1 more Smart Citation
“…Technical issues raised for internal dose assessment by WBC of Fukushima Prefecture residents were well summarized by Kurihara et al [67]. The issues can be categorized as follows: (1) setting a suitable intake scenario to estimate intake amount from measured 134 Cs and 137 Cs body content (acute or chronic, inhalation or ingestion); (2) avoiding interference by the natural radionuclide 214 Bi in 134 Cs detection (both radionuclides emit similar energies of gamma rays, which makes spectrum analysis difficult); (3) standardizing calibration and measurement procedures; (4) establishing a method for estimating 134 Cs and 137 Cs body contents of children (whole-body counters were originally designed for measuring adult radiation workers); and (5) avoiding effects on measurements due to body surface contamination.…”
Section: Issues Related To Internal Dose Assessmentmentioning
confidence: 99%
“…Considering such con-servative assumptions, internal doses estimated by WBC could be more reliable. Although estimation from WBC has issues related to the intake scenarios, the acute and chronic intake scenarios were considered both rational and appropriate assumptions for estimating individual internal doses to large populations from a single WBC measurement result [67].…”
Section: Jrprmentioning
confidence: 99%